Pathology of Gray Wolf Shoulders: Lessons in Species and Aging. Issue 10 (30th July 2016) - Lawler, Dennis; Becker, Julia; Reetz, Jennifer; Goodmann, Pat; Evans, Richard; Rubin, David; Tangredi, Basil; Widga, Christopher; Sackman, Jill; Martin, Terrence; Kohn, Luci; Smith, Gail
ABSTRACT: We examined scapula glenoids ( n = 14) and proximal articular humeri ( n = 14) of seven gray wolves that were maintained in a sanctuary park setting. Immediately after death, observations were made visually in situ and by radiography. Further observations were made in a museum laboratory setting, prior to and following clearing of soft tissues. Selected dry bone specimens were evaluated using computed tomography. Significant cartilage erosion and osteoarthropathy were identified in all shoulder joints. No single evaluation method yielded maximal information. Plain film radiography revealed only more severe changes. Computed tomography yielded more detail and clarity than standard radiography. Direct examination of articular cartilage informed about joint soft tissue, and dry bone informed about externally visible bone pathology. These data provide a basis for biological, biomedical, ecological, and archaeological scientists to improve retrospective interpretations of bone lesions. They further support developing plausible differential diagnoses for features of ancient and modern animal bones. We noted a dog‐like capacity for wolf longevity in a non‐free‐roaming environment. However, aged wolves' life spans far exceeded those of similar‐sized domestic dogs and breeds, suggesting the possibility of an important species difference that should be explored. We suggest also a hypothesis that the driving force for joint pathology in sheltered non‐domestic species may relate significantly to achieving the longevity that is possible biologically, but is uncommon in the wild because of differential stochastic influences. Anat Rec, 299:1338–1347, 2016. © 2016 Wiley Periodicals, Inc.